The Impact of Silver Nanoparticle-Induced Photothermal Therapy and Its Augmentation of Hyperthermia on Breast Cancer Cells Harboring Intracellular Bacteria - Sijia Liu; Spencer Phillips; Scott Northrup; Nicole Levi (MDPI AG, 2023)
Breast cancer can harbor intracellular bacteria, which may have an impact on metastasis and therapeutic responses. Silver nanoparticles are FDA-approved for their antimicrobial potential, plus they have pleiotropic benefits for eradicating cancer cells. In the current work we synthesized photothermal silver nanoparticles (AgNPs) with an absorption at 800 nm for heat generation when exposed to near-infrared laser irradiation. Breast cell lines MCF 10A, MCF7, and MDA MB 231 were infected with Pseudomonas aeruginosa, and their response to AgNPs, heat, or photothermal therapy (PTT) was evaluated. The results demonstrate that the application of a brief heating of cells treated with AgNPs offers a synergistic benefit in killing both infected and non-infected cells. Using 10 µg/mL of AgNPs plus laser stimulation induced a temperature change of 12 °C, which was sufficient for reducing non-infected breast cells by 81-94%. Infected breast cells were resistant to PTT, with only a reduction of 45-68%. In the absence of laser stimulation, 10 µg/mL of AgNPs reduced breast cell populations by 10-65% with 24 h of exposure. This concentration had no impact on the survival of planktonic bacteria with or without laser stimulation, although infected breast cells had a 42-90% reduction in intracellular bacteria. Overall, this work highlights the advantages of AgNPs for the generation of heat, and to augment the benefits of heat, in breast cancer cells harboring intracellular infection.